2008
DOI: 10.1111/j.1462-2920.2008.01577.x
|View full text |Cite
|
Sign up to set email alerts
|

Resting spore formation of aphid‐pathogenic fungus Pandora nouryi depends on the concentration of infective inoculum

Abstract: Resting spore formation of some aphid-pathogenic Entomophthorales is important for the seasonal pattern of their prevalence and survival but this process is poorly understood. To explore the possible mechanism involved in the process, Pandora nouryi (obligate aphid pathogen) interacted with green peach aphid Myzus persicae on cabbage leaves under favourable conditions. Host nymphs showered with primary conidia of an isolate (LC(50): 0.9-6.7 conidia mm(-2) 4-7 days post shower) from air captures in the low-lati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Considering that most field temperatures during this survey were below 108C, this phenomenon observed in a laboratory study indirectly supports our result that temperature is the main factor regulating RS production under field conditions. The survival and propagation of an obligate aphid pathogen depends on host density, and the survival strategy for P. nouryi encountering the decrease of available hosts possibly relies on increasing RS formation in vivo (Huang and Feng 2008;Zhou and Feng 2010). Thus, environmental factors that influence host population fluctuation probably regulated the level of fungal RS formation in the field.…”
Section: Biological Implicationsmentioning
confidence: 98%
See 2 more Smart Citations
“…Considering that most field temperatures during this survey were below 108C, this phenomenon observed in a laboratory study indirectly supports our result that temperature is the main factor regulating RS production under field conditions. The survival and propagation of an obligate aphid pathogen depends on host density, and the survival strategy for P. nouryi encountering the decrease of available hosts possibly relies on increasing RS formation in vivo (Huang and Feng 2008;Zhou and Feng 2010). Thus, environmental factors that influence host population fluctuation probably regulated the level of fungal RS formation in the field.…”
Section: Biological Implicationsmentioning
confidence: 98%
“…Cadavers were then squashed in lactophenol cotton blue and microscopically examined at 100) magnification to determine the presence of P. nouryi mycosis (cadavers) and RS produced in cadavers. RS were identified as spherical spores, 26.3 mm in diameter (range, 22.5Á32.5 mm), with walls 4.5 mm thick (range, 3Á5 mm), according to Huang and Feng (2008) and Keller (2006). The numbers of cadavers collected on weekly sampling occasions were recorded, and the proportions of cadavers containing RS were calculated.…”
Section: Observations Of Mycosed Aphids and Rsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a field study, Thomsen and Eilenberg [19] found that Entomophthora muscae (Cohn) Fresenius forms resting spores only in female Delia radicum (L.) and that the proportion of females with resting spores was negatively correlated with day length. Further, Huang and Feng [18] hypothesized that the resting spore formation of the aphid pathogenic fungus Pandora nouryi (Remaudière and Hennebert) Humber depends on the inoculum concentration. Later, Zhou and Feng [17] tested the effects of three parameters on the resting spore formation of P. nouryi .…”
Section: Introductionmentioning
confidence: 99%
“…Most of the fungal species never form resting spores in vivo or in vitro . Exceptionally, P. nouryi may form resting spores in vivo (Keller 2006) and was found producing azygospores in cadavers of green peach aphid, Myzus persicae , in China (Huang and Feng 2008).…”
Section: Introductionmentioning
confidence: 99%